Microbiology Test Results for White Edible Birds Nest with Fecal Contamination - Siti Gusti Ningrum; Ferdi Nur Ardiansyah; Hendra Aditiya Pratama; Hardika Dewi Erawati; Dian Ayu Kartika Sari (Universitas Airlangga, 2024)
Background: Southeast Asia's edible bird nest industry, particularly in Indonesia, has experienced rapid growth in recent years. Indonesia stands as the world's leading exporter of edible bird nests. However, concerns persist regarding the quality of edible bird nests produced in the country, specifically to do with meeting quality standards by ensuring freedom from microbial contaminants that can lead to foodborne illnesses. Purpose: To evaluate the microbiological contamination of cleaned edible bird nests sourced from Java Island, Indonesia. Cases(s): Yellow-brown discoloration of edible bird nests collected from bird houses of Javan origin. Case Management: Fifty samples of raw white edible bird’s nest samples (cup-shaped) with yellow-brown discoloration (n=25) originating from Java Island and raw white edible bird’s nest samples (cup-shaped) (n=25) were collected aseptically from the edible bird’s nest warehouses in Surabaya. These samples of edible nests from Java Island were subjected to microbiological analysis. The findings revealed a disconcerting trend, with 25 samples from Java Island exhibiting contamination by Escherichia coli (40%) and coliform bacteria (100%), surpassing established contamination thresholds. Conclusion: This raises critical concerns about the safety and quality of edible bird nests from the region, highlighting the need for enhanced production and processing practices, as well as rigorous quality control measures to ensure consumer safety and to maintain the industry's reputation on a global scale. Addressing these issues is imperative not only to safeguard public health but also to sustain and further develop the lucrative edible bird nest industry in Indonesia.